A Comparative Analysis of Clitoria ternatea Linn. (Butterfly Pea) Flower Extract as Natural Liquid pH Indicator and Natural pH Paper (Dhaka University Journal of Pharmaceutical Sciences, 2018)
Clitoria ternatea Linn (CT) or Butterfly pea flower is a blue flower edible plant, which is commonly used as food colouring. The objective of this study was to develop a liquid and paper pH indicator from CT extracts. The effectiveness of CT extract as pH indicator was evaluated by titration and product testing result against standard indicator. The stability of CT extracts were also conducted in 7 days storage. Findings from this study shows that CT extract is an effective liquid pH indicator except for weak acid samples. Whereas pH paper made from CT extract is effective as pH paper except for testing pH range from 4 -6. It is concluded thatCT extracts can be potentially effective pH indicator.Dhaka Univ. J. Pharm. Sci. 17(1): 97-103, 2018 (June)